Literature Review of Building Information Modelling (BIM) Challenges in the Development of Architecture, Engineering, and Construction (AEC) Industry - Christina, Merry; Poerwoningsih, Dina; Budiyanto, Hery (Proceedings of International Conference of Graduate School on Sustainability, 2022)
Infrastructure development is an important part of the economic transformation policy in the Industrial Era 4.0. However, there are still challenges in the Architecture, Engineering, and Construction (AEC) field in the Industrial Era 4.0, namely the need for technological development in sustainable construction, especially in infrastructure projects. The utilization of information technology is one of the strategies to improve performance and competitiveness in handling construction projects effectively and efficiently. Building Information Modelling (BIM) is an information system that processes input into information in the form of building Modelling as a tool in the decision-making process in every stage of a construction project. The research was conducted using the Literature Review method. This study concludes that BIM in Indonesia has been adopted on a limited basis and the majority of construction projects still use conventional methods. The advantages of using BIM technology are (1) able to detect conflicts/errors early or during the planning and be able to prevent them (2) makes the work process faster and minimizes human resources so that it saves costs (3) able to share information completely and quickly (4) assist in decision making during planning and design (5) help build trust and synergy between construction stakeholders and reduce risk. Obstacles in the implementation of BIM in Indonesia are (1) the regulation of governing state development does not regulate in detail the procedures and workflows and outputs of BIM implementation (2) there are still not many experts who have BIM certificates (3) The high cost of BIM investment. Keywords: advantages, Building Information Modelling (BIM), construction, obstacle factor